Direct resin composite restoration of endodontically-treated permanent molars in adolescents: bite force and patient-specific finite element analysis (Journal of Applied Oral Science, 2021)
Objective: To evaluate the influence of three levels of dental structure loss on stress distribution and bite load in root canal-treated young molar teeth that were filled with bulk-fill resin composite, using finite element analysis (FEA) to predict clinical failure. Methodology: Three first mandibular molars with extensive caries lesions were selected in teenager patients. The habitual occlusion bite force was measured using gnathodynamometer before and after endodontic/restoration procedures. The recorded bite forces were used as input for patient-specific FEA models, generated from cone-beam computed tomographic (CT) scans of the teeth before and after treatment. Loads were simulated using the contact loading of the antagonist molars selected based on the CT scans and clinical evaluation. Pre and post treatment bite forces (N) in the 3 patients were 30.1/136.6, 34.3/133.4, and 47.9/124.1. Results: Bite force increased 260% (from 36.7±11.6 to 131.9±17.8 N) after endodontic and direct restoration. Before endodontic intervention, the stress concentration was located in coronal tooth structure; after rehabilitation, the stresses were located in root dentin, regardless of the level of tooth structure loss. The bite force used on molar teeth after pulp removal during endodontic treatment resulted in high stress concentrations in weakened tooth areas and at the furcation. Conclusion: Extensive caries negatively affected the bite force. After pulp removal and endodontic treatment, stress and strain concentrations were higher in the weakened dental structure. Root canal treatment associated with direct resin composite restorative procedure could restore the stress-strain conditions in permanent young molar teeth.